Causes of Delay in MARA Management Procurement Construction Projects - Abdullah, Mohd Razaki; Abdul Rahman, Ismail; Abdul Azis, Ade Asmi (Journal of Surveying, Construction and Property, 2010)
For many years, the issue of delay in MARA management procurement construction projects has been phenomenal. Its impacts were so significant that it tends to decelerate the implementation of MARA strategic planning. This paper presents a survey study on significant causes of delay in MARA management procurement construction projects. The questionnaire used consists of identified 18 causes of delay. The study was carried out on the current 12 (38.7%) MARA construction management procurement projects scattered in peninsular Malaysia. The respondents were personnel that work as PMC (executives, resident engineers, and clerk of works) for those projects and clients (MARA state directors, project officers, and engineers). Seventy sets of questionnaire were distributed to the respondents and 58 sets (82.86%) returned. The results analysis revealed that the significant delay causes were cash flow and financial difficulties faced by contractors, contractors’ poor site management and ineffective planning and scheduling by contractors. Several steps are proposed in order to avoid delay for MARA future project. Key words: Construction delay, MARA construction projects, Majlis Amanah Rakyat